Banding Eco Sanctuary Enterprise / Muhammad Sahir A. Rahim ... [et al.] - A.Rahim, Muhammad Sahir; Kamal Huri, Sham Sany; Ishak, Mohd Rizal; Abd Manaf, Saiful Azuan; Abd Karim, Norazlina (Faculty of Sports Science and Recreation, 2002)
In managing a business we must have a unique and systematic administrative structure. A good business plan will determine the smoothness and perfection of the business. It is important as a process at integrating duty and raw material to achieve company aims, which have been stated at the earlier stage at business establishment. The administrative department function as a protractor that is responsible to expand the operational size at business. It is the pulse of a business especially in determining the capital low.